The role of amino acid metabolism in inflammatory bowel disease and other inflammatory diseases - Zheng, Xiaowen; Zhu, Yi; Zhao, Zihan; Chu, Ying; Yang, Wenjing (Frontiers in Immunology, 2023)
Inflammation is a characteristic symptom of the occurrence and development of many diseases, which is mainly characterized by the infiltration of inflammatory cells such as macrophages and granulocytes, and the increased release of proinflammatory factors. Subsequently, macrophage differentiates and T cells and other regulated factors exhibit anti-inflammatory function, releasing pro-and anti-inflammatory factors to maintain homeostasis. In the treatment of inflammatory bowel disease (IBD) and other inflammatory diseases, mesenchymal stem cells (MSCs) and their derived exosomes (MSC-EXO) have been found to show promising effects. However, the application of exosomes in treating inflammation is still ongoing, and the mechanism and therapeutic outcome are yet to b fully employed. Although reports define various degrees of metabolic disorders in both the inflamed and non-inflamed parts of inflammatory diseases, little is known about the changes in amino acid metabolism in such conditions. This review aims to summarize amino acid changes and mechanisms involved in the progression of inflammatory bowel disease (IBD) and other inflammatory diseases. Since Due to mesenchymal stem cells (MSCs) and their derived exosomes (MSC-EXO) have been found to show promising effects Iin the treatment of inflammatory bowel disease (IBD) and other inflammatory diseases, mesenchymal stem cells (MSCs) and their derived exosomes (MSC-EXO) have been found to show promising effects,.Ttheir potential in the possibility of modulation of amino acid metabolism by exosomes in the treatment of inflammation is also discussed.